Chinese Ischemic Stroke Subclassification - GAO, Shan; Wang, yongjun; Xu, anding; Li, yansheng; Wang, David (Frontiers in Neurology, 2011)
Accurate classification of stroke has significant impact on patient care and conduction of stroke clinical trials. The current systems such as TOAST, SSS-TOAST, Korean TOAST and A-S-C-O have limitations. With the advent of new imaging technology, there is a need to have a more accurate stroke subclassification system. Chinese Ischemic Stroke Subclassification (CISS) system is a new two step system aims at the etiology and then underlying mechanism of a stroke. The first step classifies stroke into five categories: large artery atherosclerosis (LAA), including atherosclerosis of aortic arch and intra-/extracranial large arteries, cardiogenic stroke (CS), penetrating artery disease (PAD), other etiology (OE) and undetermined etiology (UE). The second step is to further classify the underlying mechanism of ischemic stroke from the intracranial and extracranial large artery atherosclerosis into the parent artery (plaque or thrombosis) occluding penetrating artery, artery-to-artery embolism, hypoperfusion/impaired emboli clearance and multiple mechanisms. Although clinical validation of CISS is being planned, CISS is an innovative system that offers much more detailed information on the pathophysiology of a stroke.